HIBAH IN THE ADMINISTRATION OF ISLAMIC PROPERTY: IJTIHADI ELEMENTS AND REALITY IN MALAYSIA (UUM Journal of Legal Studies, 2019)
A guarantee of successful life in this world and the hereafter would be achieved if Muslims live according to Islamic principles and teachings. Property and power that are entrusted to men by Allah SWT ought to be judiciously administered based on Islamic precepts. In brief, the administration of Islamic property aims to achieve hasanah (goodness) not only here but also the hereafter. Islam, as a complete way of life, has outlined the absolute guidance on property administration through a systematic law, i.e. the Islamic law of inheritance by means of wasiat (will), hibah (gift inter vivos) and waqf (charity). This article focused on the instrument of hibah under the administration of Islamic property and this includes comparisons of its principles and the reality of its application in Malaysia. Hibah is an element of the distribution of assets as drawn under the Islamic concept of managing property. Its concept, application and implementation need to be intensely understood. It has been occasionally observed that disputes would take place after the demise of the donor (the person who had exercised hibah) which complicates the distribution of the assets. Therefore, if this instrument is exercised differ entry between institutions but effectively and cautiously in line with the Islamic rules and principles, the rights of those entitled would be certainly safeguarded.